Complex iron and sulphate reducing Cretaceous sedimentary system revealed by extreme isotope values. (23rd December 2021) - Gyomlai, Thomas; Fayek, Mostafa; Ferrini, Vincenzo; Mignardi, Silvano; De Vito, Caterina
Abstract: The iron and sulphur isotope compositions of sedimentary pyrites have been extensively used as a proxy for microbial metabolisms and redox evolution of the oceans. We illustrate the benefit of in‐situ and coupled study of Fe and S isotopes on sedimentary pyrites from late mid‐Cretaceous sediments from the Central Apennines, Italy. We report extremely low δ 56 Fe values for sedimentary pyrites (as low as −4.7‰) and unusual high δ 34 S values (as high as +88.9‰). We propose a model that explains these extreme values but also the large range of pyrite δ 34 S and δ 56 Fe values as well as the considerable microscale variations in this values. These isotopic compositions were likely produced by microbial dissimilatory iron reduction in the shelf sediment, transportation of Fe 2+ via an iron shuttle, production of heavy SO4 by pyrite precipitation in the water column, diffusion and advection of SO4 and H2 S, and finally bacterial sulphate reduction.